FISH DIVERSITY, COMMUNITY STRUCTURE AND ECOLOGICAL INTEGRITY OF RIVER BRAHMANI - DAS, M. K.; SAMANTA, S.; M., SAJINA A.; SUDHEESAN, DEEPA; NASKAR, M.; BANDOPADHYAY, M. K.; PAUL, S. K.; BHOWMICK, S.; SRIVASTAVA, P. K. (Journal of the Inland Fisheries Society of India, 2021)
River Brahmani is the second largest river system in Odisha and sustains rich diversity of fish and livelihood of fishers. In recent years a decline in fish catch due to various anthropogenic activities in the river basin is evident. The study analyses the present fish diversity, distribution pattern and community structure along the longitudinal gradient of the river and evaluates its ecological integrity applying a multimetric assessment method. Sixty fish species were recorded from the river, Cyprinidae being the dominant family. The middle and lower stretches of the river showed dominance of small bodied eurytopic, indigenous fish species with periodic and opportunistic life history strategies with decline of the Indian Major Carps. A trophic shift towards dominance of omnivorous species is evident. Non-metric multidimensional scaling revealed greater distribution and abundance of fish species with increasing river depth, along the river gradient. Assessment of biotic integrity showed that 27 % of the sampling sites in the river supported fish assemblage in acceptable condition. Key words: River Brahmani, fish diversity, community structure, ecological integrity